Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content: 1. The method of Imam Al-Damiry (D. 808 AH) in Al-Jarh and Al-Ta’deel through his book Al-Najm Al-Wahaj fi explain Al-Minhaj Mr. Abdulsalam Hezam Musaed Al-Lahabi 2. Doctrine (Fekh) matters that have been discussed by Imam Alnasser Leddinullah Alhassan bin Ali Nin Dawood Almoayadi (died in 1026) in his justification for some holy verse of Quran from Alfurqan and Al-Zukruf Dr. Abduljalil Mahyoub Fadel 3. The accepted narrators who were weak in them because of their sheikhs in Ibn Uday’s book Al-Kamil - An inductive and analytical study Mr. Anwar Mahmoud bin Latif , Dr. Fouad Bouneama 4. Imam Ismail bin Al-Qasim and his manuscript (Mas’alat Talaq Aldawr): study and investigation Mr. Jamil Ghaleb Ahmed Al-Lahji 5. Rights to be Deducted from the Capital of the Decedent’s Inheritance and those Apportioned from One Third of the Estate Dr. Mohammed Saleh Mohammed Haj 6. Narratives of the Tribe of Hamadān on the Prophet Mohammed (peace be upon him) - Collection and Study. Dr. Abdullah Rajeh Sharib 7. Ibn Mozaffar AI-Yemeni and His BooK " Al-Kawākib Al-Nayyirah" (Study and Veriflcation of Revocability and Difference Parts) Mr. Ramzi Abbas Ahmed Muhammad AI-Awadi 8. Moderation in the light of Islamic Sharia Prof. Dil Aqa Waqar, Mr. Sayid Ahmad Hashimy 9. The standards of architecture in The Holy Quran Dr. Maryam Hussain Alsada